Limnochemistry and Plankton Diversity in Some High Altitude Lakes of Kashmir Himalaya - Islam, Sheikh Tajamul; Dar, Shahid Ahmad; Sofi, Mohd Sharjeel; Bhat, Sami Ullah; Sabha, Inam; Hamid, Aadil; Jehangir, Arshid; Bhat, Aftab Ahmad (Frontiers in Environmental Science, 2021)
High altitude lakes (HALs) of Kashmir Himalaya are the important ecosystems in the mountain ecology of the broader Hindukush Himalayan region. This article provides a comprehensive information about the plankton (phytoplankton and periphyton) assemblages, water quality (WQ), bathymetry, morphometry, and land use land cover (LULC) of some select high altitude mountain lakes of Kashmir Himalaya. LULC analysis revealed that the catchment of the lakes spread over an area of about 16179 ha, is covered by different land cover types dominated by pastures (50.8%), followed by barren rocky (32.6%), snow and glaciers (11.9%), lakes (2.5%), forest (2%), and streams (0.2%). Bathymetric and morphometric analysis revealed that the Gangbal Lake is the deepest (84 m) and largest (162.4 ha) among the investigated lakes. The water quality index revealed that all the HALs have the excellent water quality category. Statistical analysis (Wilk’s λ) depicted that nitrate-nitrogen (NO3--N), nitrite nitrogen (NO2--N), ammoniacal nitrogen (NH3-N)), total phosphorus (TP), and magnesium hardness (Mg-H) are responsible for major variability between all HALs sites. The cations in decreasing order of concentration were Ca2+ ˃ Mg2+ ˃ Na+ ˃ K+ while as anions in decreasing order of concentration were HCO3- ˃ Cl- ˃ SO42-. Algal composition (phytoplankton and periphyton) revealed the presence of 61 taxa belonging to Bacillariophyceae (45), Chlorophyceae (14), Cyanophyceae (1), and Xanthophyceae (1). The higher dominance of Bacillariophyceae indicates oligotrophic nature of the lakes. Canonical correspondence analysis (CCA) highlighted the role of various water quality parameters like pH, EC, and TDS on the composition of phytoplankton and periphyton species among the lakes. The present study therefore generated a baseline database for some of the HALs of Kashmir Himalaya that can act as a precursor for more research on for assessing future changes in the lake ecosystems of the region.